Whole-body β-oxidation of 18:2ω6 and 18:3ω3 in the pig varies markedly with weaning strategy and dietary 18:3ω3 - Richard P. Bazinet; Ewen G. McMillan; Ravi Seebaransingh; Anthony M. Hayes; Stephen C. Cunnane (Journal of Lipid Research, 2003)
Segregated early weaning (SEW) into a cleaner nursery increases food intake and growth in pigs, presumably because of reduced immune stimulation compared with conventionally reared, nonsegregated pigs (NSW). The aim of the present study was to evaluate the oxidation of linoleic acid (18:2ω6) and α-linolenic acid (18:3ω3) in SEW and NSW pigs. Pigs consumed a control or high 18:3ω3 diet (ω6 PUFA/ω3 PUFA; 21.3 vs. 2.5, respectively) and were weaned at either 14 days old into a SEW nursery or at 21 days old into a conventional NSW nursery. The major acute-phase protein of pigs but not haptoglobin increased in 35-day-old NSW pigs. NSW pigs had 15–25% lower carcass 18:2ω6 and 20–30% lower carcass 18:3ω3 (% composition) at 49 days old. Between 35- and 49-days-old, NSW pigs had a higher whole-body oxidation of 18:2ω6 (40–120%) and 18:3ω3 (30–80%). The high 18:3ω3 diet decreased the whole-body oxidation of 18:2ω6 by 73% and of 18:3ω3 by 63% in NSW pigs.We conclude that moderately cleaner housing SEW significantly decreases 18:2ω6 and 18:3ω3 oxidation in pigs.